Common carotid arteritis and polymyalgia with Mycoplasma pneumoniae infection. Issue 4 (April 2019) - Takahashi, Ippei; Ishihara, Masayuki; Oishi, Taku; Yamamoto, Masaki; Narita, Mitsuo; Fujieda, Mikiya
Abstract: A few pediatric cases with brain vasculitis most frequently affecting the middle cerebral artery have been reported in association with Mycoplasma pneumoniae infection, but involvement of the common carotid artery (CCA) before the bifurcation has not been reported to date. We report herein a case of 10-year-old boy with common carotid arteritis and polymyalgia associated with Mycoplasma pneumoniae infection. His fever and cough began 2 weeks before, and his right upper and lower extremity pains began 2 days before admission. He had initially been treated with clarithromycin followed by tosufloxacin, but his symptoms persisted. His M. pneumonia –specific antibody titer was high on admission (1:10240 by particle agglutination method) and the gene of M. pneumoniae was detected in a throat swab specimen by the loop-mediated isothermal amplification method with initial high levels of serum interleukin-8, tumor necrosis factor-α, and interleukin-18 along with elevated blood levels of complements. On the 5th day of hospitalization, vascular echograms of the extremities and neck showed increasing intima-media thickness of bilateral CCAs without stenosis and/or thrombosis and T2-weighted with lipid suppression magnetic resonance imaging of the neck showed high signal intensity of bilateral CCA walls. Coagulation studies were unremarkable and no autoantibodies were detected as far as tested. He was successfully treated by intravenous administration of prednisolone and was stable without any neurological sequelae 17 months after the onset without medication. His particle agglutination titer decreased to 1:5120, and serum interleukin-8, tumor necrosis factor-α, interleukin-18, and complement levels returned to normal.